The Implementation of BIM Tekla Structure on Quantity Take Off for Structural Works of X Building Project - Eka Aprillia; I Nyoman Dita Pahang Putra (Jurnal Teknik Sipil, 2024)
BIM technology in the construction world is growing. However, the application of BIM in Indonesia has not been carried out thoroughly. BIM technology can help quantity take off work that affects the success or failure of a project. BIM can reduce the error rate of quantity take off planning calculations compared to manual calculations. Tekla Structure is one of the software developments of BIM that can produce quantity take off building output along with 3D visualisation. This research conducts 3D modelling and discusses the comparison of quantity take off using BIM-based software Tekla Structures with a recap of the manual calculation contained in the initial Bill of Quantity for the X Building Project planning. This difference can be used as a consideration for the application of BIM in the initial calculation of project planning. The percentage difference obtained for the pile cap resulted in concrete volume deviation of 0.69% and -19.1% for reinforcement volume. The spun piles work resulted in a concrete volume deviation of -0.8% and reinforcement volume of 8.45%. In the calculation of column work, the deviation value for concrete volume is 3.14%, while the volume of reinforcement is -12.2%. The results of the BIM quantity take-off are deemed more reliable due to the 3D visualization of BIM objects and the ability to adjust the detail of work elements.